P114 Frequent work productivity and activity impairment in caregivers of children with inflammatory bowel disease: a project of the prospective PIBD-SETQuality inception cohort study. (27th May 2021) - Klomberg, R; Kemos, P; Aardoom, M; Rizopoulos, D; Croft, N; de Ridder, L; Neyt, M
Abstract: Background: Paediatric inflammatory bowel disease (IBD) can disrupt daily lives of patients and their caregivers, who may be impaired in performing work or daily activities due to increased caretaking responsibilities, accompanying to frequent hospital visits and increased school absence of their children. However, literature on these impairments is sparse. The aims of this study were to longitudinally quantify this work and activity impairment and evaluate associated factors. Second, to assess the impact of these impairments on caregiver's health-related quality of life (HRQoL). Methods: Since January 2017, children with newly diagnosed IBD are included for the international prospective PIBD-SETQuality inception cohort study 1 . Patient and disease characteristics are collected at time of diagnosis, at three and twelve months. The impact of the child's IBD on caregiver's socioeconomic functioning and HRQoL (rate 1–10) is longitudinally evaluated by the Work Productivity and Activity Impairment (WPAI) and EQ-5D-5L questionnaire. Primary outcomes, including absenteeism (percentage work time missed), presenteeism (percentage impairment while working), work productivity loss (percentage overall work impairment) and activity impairment (percentage affected daily activities, such as householding or exercise), were evaluated using generalized estimating equations models. Results: Up to February 2021, 436 children (247 Crohn's disease (CD); 169 ulcerative colitis (UC)/IBD-unclassified (IBDU)) were eligible for analysis of the WPAI questionnaire. Mean employment rate at diagnosis was 81.0% (74.8% CD, 86.0% UC/IBD-U, p=0.050). At diagnosis, mean absenteeism, presenteeism, work productivity loss and activity impairment were 28.0%, 31.4%, 46.4% and 36.5% respectively (Figure 1A-D). Work productivity loss and activity impairment significantly decreased over time and were associated with disease activity, but not with IBD diagnosis or age at diagnosis (Figure 2A-B). Work productivity loss, but not activity impairment was negatively associated with HRQoL (β -0.067, p<0.01; β -0.027, p=0.387 respectively). Estimated costs related to absenteeism associated with the child's disease were €8711 per patient during the first year after diagnosis. Conclusion: Parents of children with IBD experience significant impairments in their work and daily activities. The impact is biggest at diagnosis, plateaus thereafter and is associated with disease activity. Work productivity impairment results in indirect costs and reduced HRQoL. Reference: Aardoom, M.A., et al., International prospective observational study investigating the disease course and heterogeneity of paediatric-onset IBD: the protocol of the PIBD-SETQuality inception cohort study. BMJ Open, 2020. Figure 1 Figure 2